Frequency of serum anti-cysticercus antibodies in the population of a rural Brazilian community (Cássia dos Coqueiros, SP) determined by ELISA and immunoblotting using Taenia crassiceps antigens - BRAGAZZA, Lúcia M.; VAZ, Adelaide J.; PASSOS, Afonso D.C.; TAKAYANAGUI, Osvaldo M.; NAKAMURA, Paulo M.; ESPÍNDOLA, Noeli M.; PARDINI, Alessandra; BUENO, Ednéia C. (Revista do Instituto de Medicina Tropical de São Paulo, 2002)
Considering the impact of cysticercosis on public health, especially the neurologic form of the disease, neurocysticercosis (NC), we studied the frequency of positivity of anti-Taenia solium cysticercus antibodies in serum samples from 1,863 inhabitants of Cássia dos Coqueiros, SP, a municipal district located 80 km from Ribeirão Preto, an area considered endemic for cysticercosis. The 1,863 samples were tested by enzyme linked immunosorbent assay (ELISA) using an antigenic extract from Taenia crassiceps vesicular fluid (Tcra). The reactive and inconclusive ELISA samples were tested by immunoblotting. Of the 459 samples submitted to immunoblotting, 40 were strongly immunoreactive to the immunodominant 18 and 14 kD peptides. Considering the use of immunoblotting as confirmatory due to its high specificity, the anti-cysticercus serum prevalence in this population was 2.1%.